Removal of Cr(VI) from wastewater by FeOOH supported on Amberlite IR120 resin. Issue 38 (14th August 2016) - Wu, Shijiao; Fu, Fenglian; Cheng, Zihang; Tang, Bing
Abstract: Resin-supported FeOOH (R-FeOOH) was synthesized by the chemical reaction of Fe 3+ -exchange resin with H2 O2 . R-FeOOH was characterized with scanning electron microscopy and X-ray powder diffraction. The optimum R-FeOOH was synthesized in the presence of 0.5 mol/L Fe 3+ and 0.09 mol/L H2 O2 . Then, R-FeOOH was employed to remove Cr(VI) from aqueous solutions under different conditions. The results indicated that the removal efficiencies of Cr(VI) were all over 98% for initial Cr(VI) concentration of 20.0 mg/L at initial pH of 2.0, 3.0, 5.0, and 7.0, with R-FeOOH dose of 15.0 g/L after reaction for 120 min. The Cr(VI) removal efficiency can attain 100% at pH 3.0 after reaction for 90 min. Besides, a test on the reuse of the R-FeOOH was conducted. The removal of Cr(VI) by R-FeOOH was through adsorption, ion exchange, and reduction. R-FeOOH can be an effective agent for Cr(VI) removal from wastewater.